2010
DOI: 10.1073/pnas.1009010107
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I (apoA-I) and apoA-I mimetic peptides inhibit tumor development in a mouse model of ovarian cancer

Abstract: We examined whether reduced levels of Apolipoprotein A-I (apoA-I) in ovarian cancer patients are causal in ovarian cancer in a mouse model. Mice expressing a human apoA-I transgene had (i) increased survival (P < 0.0001) and (ii) decreased tumor development (P < 0.01), when compared with littermates, following injection of mouse ovarian epithelial papillary serous adenocarcinoma cells (ID-8 cells). ApoA-I mimetic peptides reduced viability and proliferation of ID8 cells and cis-platinum-resistant human ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
186
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(220 citation statements)
references
References 53 publications
19
186
6
Order By: Relevance
“…Both apo A-I as well as apo A-I mimetic peptides have the ability to bind pro-inflammatory phospholipids like LPA [41], but the apo A-I mimetic peptides bind LPA with a greater affinity than apo A-I, causing their removal from serum and lowering their serum levels. Thus apo A-I controls the rate of cell proliferation in a tumor and the tumor growth [42].…”
Section: Anti Tumor Activity Of Apo A-imentioning
confidence: 99%
“…Both apo A-I as well as apo A-I mimetic peptides have the ability to bind pro-inflammatory phospholipids like LPA [41], but the apo A-I mimetic peptides bind LPA with a greater affinity than apo A-I, causing their removal from serum and lowering their serum levels. Thus apo A-I controls the rate of cell proliferation in a tumor and the tumor growth [42].…”
Section: Anti Tumor Activity Of Apo A-imentioning
confidence: 99%
“…If much higher doses of peptide will be required in vivo in humans, the cost of producing the peptide may limit the utility of these peptides as clinical therapeutic agents in diseases for which lower-cost treatments are currently effective. A recent publication from our laboratory ( 18 ) demonstrates that the 4F peptide binds lysophosphatidic acid (which induces migration and invasion of both mouse and human epithelial ovarian cancer cells) with extraordinary affi nity (K d = 0.000523 ± 0.0015 nM). It was demonstrated that administering L-4F orally (added to mouse chow at a dose of 100 mg/kg/day) to mice with a normal immune system that had been injected with mouse ovarian epithelial cancer cells signifi cantly reduced both plasma levels of lysophosphatidic acid and tumor burden ( 18 ).…”
Section: Hs-crpmentioning
confidence: 99%
“…A recent publication from our laboratory ( 18 ) demonstrates that the 4F peptide binds lysophosphatidic acid (which induces migration and invasion of both mouse and human epithelial ovarian cancer cells) with extraordinary affi nity (K d = 0.000523 ± 0.0015 nM). It was demonstrated that administering L-4F orally (added to mouse chow at a dose of 100 mg/kg/day) to mice with a normal immune system that had been injected with mouse ovarian epithelial cancer cells signifi cantly reduced both plasma levels of lysophosphatidic acid and tumor burden ( 18 ). Assuming that high doses of the 4F peptides will be required, assuming that the cost of production of such peptides will be high, and even assuming that hs-CRP levels would be elevated when the peptide was administered at high doses orally (which seems less likely), the use of these peptides in the treatment of diseases with an unmet clinical need such as ovarian cancer could still be attractive.…”
Section: Hs-crpmentioning
confidence: 99%
“…Zhang et al (25) analyzed the lipid levels of 206 patients with colorectal cancer, 70 patients with benign colorectal disease, and 300 healthy participants, and revealed that serum ApoA-I and ApoB levels were significantly lower in colorectal cancer patients (25). In addition to colon cancer, ApoA-I inhibited tumor development in a mouse model of ovarian cancer (26). Significantly decreased serum levels of ApoA-I were found in patients with cholangiocarcinoma (27), and increased levels in serum were associated with a favorable prognosis in patients with metastatic nasopharyngeal carcinoma (28).…”
Section: Discussionmentioning
confidence: 99%